Research on the Integration and Application of Computer Technology in the Construction of Ship Inspection System - Liang, Lunchang (International Journal of Computer Science and Information Technology, 2025)
This study aims to explore the integrated application of computer technology in ship inspection systems. With the rapid development of information technology, the application of computer technology in various industries is becoming increasingly widespread, and the shipbuilding industry is no exception. This study proposes a solution for the integration and application of ship inspection systems and computer technology by analyzing the current situation and requirements of ship inspection systems, combined with the latest developments in computer technology. This plan aims to improve the efficiency and accuracy of ship inspection, achieve data-driven management and information sharing, enhance the traceability of the inspection process, and promote technological innovation and industrial upgrading in the shipbuilding industry, and is expected to provide strong support for the sustainable development of the shipbuilding industry.